Collaboration in Blended Learning: An EFL Students’ Perspectives - Irpan Apandi Batubara (International Journal of English and Applied Linguistics (IJEAL), 2024)
Blended learning becomes very popular in the EFL context after the adoption of technology into language teaching and learning. This study aimed to explore EFL students’ perspectives of collaboration in blended learning. This study applied qualitative study in a private university in North Sumatra, Indonesia. The data collection was conducted through semi-structured interviews that involved 12 EFL students from a private university in Medan, Indonesia. The data were analysed using inductive approach. The raw data were condensed and coded into several categories. The findings revealed students’ perceptions on the comparison between face to face and online learning, the urgency of students’ collaboration in blended learning, and the factors that affected students’ blended learning collaboration. The students’ perspective figured out students’ experience in doing collaboration in face to face and online setting. Furthermore, the factors that affected the collaboration in blended learning were identified. The findings of this study contributes to the improvement of EFL teaching practice in blended learning settings.